Strain typing and vaccine development for chancroid. - Leduc, Isabelle. (University of Ottawa (Canada), 2001)
Haemophilus ducreyi is the causative agent of chancroid, a sexually transmitted genital ulcer disease shown to be involved in the heterosexual transmission of the human immunodeficiency virus. Heterogeneity of H. ducreyi lipooligosaccharide (LOS), complex sugars present in the bacterial membrane, was investigated to explore a potential basis for a classification system. A panel of clinical H. ducreyi isolates could be classified into 7 groups (1 to 7) according to the number and intensity of the LOS bands after electrophoresis, and grouped into 5 categories (A through E) according to the specific reaction and cross-reaction of antisera raised to outer membrane proteins (OMP). Carbohydrate and mass spectrometry analyses confirmed that all strains studied expressed many different LOS glycoforms at the cell surface, and that strains belonging to serologic categories B and D expressed truncated LOS molecules and lacked the characteristic DD-heptose found only in H. ducreyi strains. The vaccine potential of the native (rHgbA) and recombinant forms (rHgbA) of the hemoglobin receptor of H. ducreyi as well as the recombinant form of the outer membrane protein D15 (rD15) were evaluated in the temperature-dependent rabbit model of chancroid . Rabbits were immunized twice, 4 weeks apart, with 100 mug of the immunogens (rHgbA, rHgbA, rD15, PBS and rFetA) in Freund's adjuvant, and challenged 4 weeks after the booster immunization with strains 35000 (homologous) and V1157 (heterologous) in doses ranging from 10 3 to 103 CFU. rHgbA vaccination modified the course of a homologous challenge at an inoculation of 103 CFU: fewer rabbits developed any ulcers, which were culture positive for a shorter period of time than in controls. After heterologous infection with 104 CFU of broth-grown strain V1157, none of the lesions of nHgbA-vaccinated rabbits developed into ulcers and lesion aspirates were sterile, while 2/3 of controls had ulcers. The rHgbA vaccine also modified the course of an experimental homologous infection, although results were very inconsistent from experiment to experiment. Indeed, across all experiments only the duration of ulcers was significantly reduced in rHgbA-vaccinated animals compared to controls at a 104 CFU inoculum. After a heterologous challenge with 104 CFU of H. ducreyi strain V1157, no lesions ulcerated in rHgbA-vaccinated animals. Modest protection similar to the rHgbA vaccine was obtained when animals were immunized with rD15. In terms of protection, there appeared to be different performance indifferent experiments: although rD15 provided partial protection against a homologous challenge infection in some experiments, it failed to protect animals against disease in others. After a homologous challenge with 104 CFU of H. ducreyi strain 35000, only the duration of ulcers were reduced in rD15-vaccinated animals compared to controls. However, across all experiments, better protection in rD15-vaccinated animals was associated with a greater humoral response to vaccine. In conclusion, rHgbA seems to be the best of these vaccine candidates against chancroid, while more experiments are needed to determine the potential of rHgbA and rD15 vaccines.
Keywords: Biology, Microbiology.